2013
DOI: 10.4049/jimmunol.1203198
|View full text |Cite
|
Sign up to set email alerts
|

Antibody and Antigen Contact Residues Define Epitope and Paratope Size and Structure

Abstract: A total of 111 Ag–Ab x-ray crystal structures of large protein Ag epitopes and paratopes were analyzed to inform the process of eliciting or selecting functional and therapeutic Abs. These analyses illustrate that Ab contact residues (CR) are distributed in three prominent CR regions (CRR) on L and H chains that overlap but do not coincide with Ab CDR. The number of Ag and Ab CRs per structure are overlapping and centered around 18 and 19, respectively. The CR span (CRS), a novel measure introduced in this art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
54
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(57 citation statements)
references
References 34 publications
3
54
0
Order By: Relevance
“…Paratopes of antibodies are the regions that directly recognize and bind to antigens. We estimated the paratope using contact-residue regions observed in antibody-antigen crystal structures (35). We calculated the net charge, solvent-accessible surface area (SASA), and hydrophobic solvent-accessible surface area (hSASA) over the computationally estimated contact-region paratopes (CR-paratopes), and we analyzed framework regions (FR) for conformational similarities and differences at the repertoire level (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Paratopes of antibodies are the regions that directly recognize and bind to antigens. We estimated the paratope using contact-residue regions observed in antibody-antigen crystal structures (35). We calculated the net charge, solvent-accessible surface area (SASA), and hydrophobic solvent-accessible surface area (hSASA) over the computationally estimated contact-region paratopes (CR-paratopes), and we analyzed framework regions (FR) for conformational similarities and differences at the repertoire level (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 1,000 trajectories were modeled per antibody; the lowest-scoring models, as evaluated by the Rosetta scoring function, were chosen for visual inspection and further analysis. The CR-paratope comprised residues that were part of the contact region of each antibody as defined by Stave et al (35). These consisted of V H residues numbered 26-33 (CDR-H1), 50-58 (CDR-H2), and 94-101 (CDR-H3) and V L residues 27-32 (CDR-L1), 49-56 (CDR-L2), and 91-96 (CDR-L3) in the Chothia numbering scheme.…”
Section: Discussionmentioning
confidence: 99%
“…One explanation for the increased efficacy observed from the TT- 1 high density conjugates and the intermediate densities of CRM 197 - 1 is that the antibodies induced were able to bind more than one hapten in the antibody binding site leading to the ability to sequester more heroin molecules. Based on analysis of 111 antigen-antibody X-ray structures, Stave and Lindpaintner 28 reported that the average number of antigen residues that contact the antibody was 18 and that the average antibody residues contacting the antigen was 21. Since heroin (369 Da) is approximately 3 times the mass of an amino acid (110 Da), this suggests that the average antibody binding site could theoretically accommodate up to 6 haptens.…”
Section: Discussionmentioning
confidence: 99%
“…The murine V L and V H domains of mPB10 were humanized by performing multiple alignments against the IMGT human V gene database. The native murine framework residues were selectively replaced with human framework residues, being mindful of potential contact amino acids that can span framework (FR) and complementarity determining region (CDR) junctions (14). More specifically, the murine variable region of PB10 was compared to human germ line V genes by using IgBLAST (15).…”
mentioning
confidence: 99%
“…Single amino acid mutations were introduced into the PB10 V H and FR regions, based on the frequency with which the substitution was found in human germ line genes. FR/CDR junctions were also inspected but rarely altered, due to their potential to act as contact residues (14). The final complete sequence (variable and constant) of hPB10 was deemed to be Ͼ90% human based on this analysis.…”
mentioning
confidence: 99%